Analisis Kombinasi Metode Algoritma MFEP dan AHP Pada Pemilihan Bibit Unggul Kopi Robusta - Asep Syaputra (Komputika : Jurnal Sistem Komputer, 2022)
Pagar Alam city as an area whose citizens are mostly farmers. The most widely grown commodities in the region are coffee and vegetables. Therefore, the area is suitable to be used as a research area and to conduct a baseline assessment of local crops, especially Robusta coffee farming. The use of Multi-Factor Evaluation Process (MFEP) and Analytical Hierarchy Process (AHP) methods is particularly suitable if applied to decision support system research. This method was chosen because it is possible to choose the best option from a variety of options. In this case, the choice in question is a suitable seedling for planting by farmers based on the specified criteria. The investigation was conducted by determining the weight value for each attribute, followed by a computational process to determine optimal criteria and alternatives, namely superior seedlings of robusta coffee that are worth cultivating. With this research that implements a combination of Multifactor Evaluation Process (MFEP) and Analitycal Hierarchy Process (AHP) methods and with object-oriented design using Unified Modeling Language (UML) will facilitate the Natural Fence City Agriculture Office and Robusta coffee farmers in choosing the right coffee seeds to grow so that coffee farmers can achieve satisfactory results.